Value of preparticipation cardiovascular evaluation of master athletes by self-reported symptoms and cardiovascular risk-score - Grimsmo, J.; Haugaa, K. H.; Popovic, I.; Lie, Ø. H.; Solberg, E. E. (Scandinavian Cardiovascular Journal, 2025)
Purpose The risk of sudden cardiac death (SCD) is increased during endurance competitive sports. Coronary artery disease (CAD) is the most common cause of SCD in master athletes = 35 years old (MAs). To reduce the risk of SCD self-assessment of symptoms by questionnaire, and evaluation of cardiovascular risk-score, are recommended as pre-participation cardiovascular evaluation (PCVE). We aimed to examine whether PCVE predicts CVD in MAs with or without increased risk as measured by validated score instruments.